The idea of retribution in the book of Ezekiel - Wong, Ka Leung. (Supplements to Vetus Testamentum,, 2001)
The objective of the book is to examine the idea of retribution in the Book of Ezekiel. The book seeks to show that underlying Ezekiel are three principles of retribution: covenant, the disposal of impurity, and poetic justice. That is to say, the consequence of an act is either governed by the terms of a covenant, or seen as the disposal of impurity produced by the act, or made to look like the act by incorporating some features of the act. The present study shows that retribution can be juridical in nature as in the case of the covenant, but it can also be non-juridical as in the cases of disposal of impurity and poetic justice. This study also provides an examination of these three important ideas seldom noted in detail in current literature on Ezekiel.